Seroprevalence of antibodies IgG/IgM anti-T. gondii in women of Coro, Venezuela - Saúl-García Yotsabeth; Martínez-Leal Coromoto; Semprún-Hernández Neomar; Martínez-Méndez Dilia (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Abstract: Studies show a high frequency of IgG against T. gondii. The aim was to evaluate the seroprevalence of IgG and IgM anti-T. gondii in 522 women. 13% of seropositivity IgG+/IgM- and 0.7% IgG+/IgM+ was found. This could be due to the climate characteristics who may decrease the transmission. We recommend the evaluation if the environmental may affect the viability of the oocysts. Resumen: Los estudios muestran una alta frecuencia de IgG contra T. gondii. El objetivo fue evaluar la seroprevalencia de IgG y IgM anti-T. gondii en 522 mujeres. Se encontró 13% de la seropositividad IgG +/IgM- y 0,7% IgG+/IgM+. Esta frecuencia podría deberse a las características del clima. Recomendamos estudiar si el medio ambiente puede afectar la viabilidad de los ooquistes.